Genetic variation in nuclear and mitochondrial markers supports a large sex difference in lifetime reproductive skew in a lekking species. Issue 18 (3rd September 2014) - Verkuil, Yvonne I.; Juillet, Cedric; Lank, David B.; Widemo, Fredrik; Piersma, Theunis
Abstract Sex differences in skews of vertebrate lifetime reproductive success are difficult to measure directly. Evolutionary histories of differential skew should be detectable in the genome. For example, male‐biased skew should reduce variation in the biparentally inherited genome relative to the maternally inherited genome. We tested this approach in lek‐breeding ruff (Class Aves, Philomachus pugnax) by comparing genetic variation of nuclear microsatellites (θn; biparental) versus mitochondrial D‐loop sequences (θm; maternal), and conversion to comparable nuclear (Ne) and female (Nef) effective population size using published ranges of mutation rates for each marker (μ). We provide a Bayesian method to calculate Ne (θn = 4Neμn) and Nef (θm = 2Nefμm) using 95% credible intervals (CI) of θn and θm as informative priors, and accounting for uncertainty in μ. In 96 male ruffs from one population, Ne was 97% (79–100%) lower than expected under random mating in an ideal population, where Ne:Nef = 2. This substantially lower autosomal variation represents the first genomic support of strong male reproductive skew in a lekking species.